Higher-Order Thinking Skill Oriented Learning: Are Teachers and Students Ready? - Nurhayani Nurhayani; Heri Retnowati (Universitas Swadaya Gunung Djati, 2022)
Abstract. Higher-Order Thinking Skill is an important ability possessed by every individual. One effort to improve this ability is to teach it in school. This phenomenological research aims to describe the extent of teachers and students' readiness to apply higher-order thinking skill-oriented learning. This study included 16 mathematics teacher respondents from 16 different schools in 12 different cities in Indonesia. The data in this study were obtained by distributing google form links using open questions to several mathematics teachers. The analysis technique in this study uses thematic analysis by gathering information from respondents into several main points. The results showed that several things must be considered to improve the readiness of teachers and students in implementing higher order thinking skill oriented learning. Some of these things include: 1) teacher awareness, 2) teacher ability about higher order thinking skill, 3) use of learning models/methods, 4) presentation of questions, 5) higher order thinking skill question concepts, 6) concepts of student understanding, 7) students' abilities about higher order thinking skill, 8) student interest, 9) time allocation, and 10) learning resources.Keywords: higher order thinking skill, others fact, teacher, student.